IMPLEMENTASI KEBIJAKAN PERATURAN PELAYANAN MANAJEMEN KEPENSIUNAN Tinjauan Implementasi Peraturan Direksi Nomor PD- 12/DIR/2012 PT.TASPEN (Persero) Denpasar - Natalia, Anak Agung Ayu Primayuni; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Regulation of the Board of Directors Number: PD-12/DIR/2012 servers regulations used by PT. TASPEN (Persero) as guidelines for the implementation of main duties and their functions to manage Pension Program including Retirement Saving Program, and Participant Data Management to Retired Civil Servants. Regulation of the Board of Directors is also used to recommend the success and failure of service regulations established by PT. TASPEN (Persero) related to post-retirement reforms (pensions). This study used a qualitative descriptive method. With the interactive model analysis by Milles and Huberman (1992), which consists of three components of analysis, namely the analysis of data reduction, data presentation and drawing of a conclusion. The writer conducted direct interviews and observation by looking directly at the phenomena that occured in the field. The results of the study is the implementation of program services and superannuation pension run by PT. TASPEN (Persero) Branch of Denpasar has been going well and in accordance with the policies set out in the Directors Rule Number: PD-12/DIR/2012. However, implementation has encountered several obstacles that hindered the implementation of services to participants such as pension file management and participant data management. The role TASPEN in providing solutions related to constraints that occur is through some form of socialization strategies that direct services, socialization with the use of electronic and printed media, external and internal reconciliation routine as well as financial reconciliation and ease of service benefit from their services customers visits, e-banking, MOBTAS services, and 1 hour services. Keywords: Policy Implementation of Service Regulations, Retirement Management, Regulation of the Board of Directors Number: PD-12/DIR/2012 PT. TASPEN (Persero)IMPLEMENTASI KEBIJAKAN PERATURAN PELAYANAN MANAJEMEN KEPENSIUNAN Tinjauan Implementasi Peraturan Direksi Nomor PD- 12/DIR/2012 PT.TASPEN (Persero) Denpasar